Fabrication of silver-decorated sulfonated polystyrene microspheres for surface-enhanced Raman scattering and antibacterial applications. Issue 85 (16th September 2015) - Zhao, Kai; Zhao, Jie; Wu, Chengjiao; Zhang, Shengwen; Deng, Ziwei; Hu, Xiaoxi; Chen, Mingli; Peng, Bo
<x xml:space="preserve">Abstract</x> A facile approach was presented to prepare SPS@Ag composite microspheres with surface-enhanced Raman scattering properties and enhanced antibacterial activities.